2015
DOI: 10.18203/issn.2454-5929.ijohns20150902
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of benign vocal fold lesions in a tertiary health centre

Abstract: <p class="abstract"><strong>Background:</strong> The present study was carried out to analyze the factors associated with different vocal fold lesions and to diagnose various benign vocal fold lesions at an early stage by their demographic profile and clinical presentations.</p><p class="abstract"><strong>Methods:</strong> Patients with history of hoarseness of voice as a predominant symptom, cough, pain, foreign body sensation, dryness of throat and with a dominant hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Our study correlates with Saha et al, who also found the largest subset comprised of vocal nodules, seen in about 60% of patients and the second most common pathology is vocal fold polyp seen in 20% of patients [11]. Siddapur et al also found that vocal nodules are the most common benign vocal fold lesions but with a lower incidence rate of 35% observed in their study [12]. Mahesh et al reported an incidence of 28.57% and 24%, of vocal nodules and vocal polyps respectively [13].…”
Section: Discussionsupporting
confidence: 91%
“…Our study correlates with Saha et al, who also found the largest subset comprised of vocal nodules, seen in about 60% of patients and the second most common pathology is vocal fold polyp seen in 20% of patients [11]. Siddapur et al also found that vocal nodules are the most common benign vocal fold lesions but with a lower incidence rate of 35% observed in their study [12]. Mahesh et al reported an incidence of 28.57% and 24%, of vocal nodules and vocal polyps respectively [13].…”
Section: Discussionsupporting
confidence: 91%
“…Kotby et al [6] reported similar results. In studies by Kambic et al [7] and Chopra et al [8] the incidence varied from 68.3 to 16%. We observed that maximum incidence of benign lesions were in the age group of 41 -50 years which is considered important period of life.…”
Section: Discussionmentioning
confidence: 93%
“…Kotby et al [6] reported similar results. In studies by kambic et al [7] and Chopra et al [8] the incidence varied from 68.3 to 16%.…”
Section: Discussionmentioning
confidence: 92%